Case Report: Chronic Suppurative Otitis Media Bilateral - Syifa Fadlilah, Syifa Fadlilah; Indah Trisnawaty; Hastuti Rahmi (Jurnal Kesehatan dan Kedokteran, 2026)
Chronic Suppurative Otitis Media (CSOM) is a persistent middle ear infection characterized by tympanic membrane perforation and prolonged or recurrent ear discharge lasting more than two months. Objective: This case report aims to analyze the clinical presentation and management approach in a patient with CSOM, as well as to evaluate the success of type II endoscopic tympanoplasty in repairing tympanic membrane perforation and restoring hearing function. Methodology: This case study utilized a qualitative approach, collecting data through physical examination, audiometric testing, and CT imaging to assess the condition of the patient's ears. The patient underwent type II endoscopic tympanoplasty on the right ear. Findings: A 52-year-old female patient presented with bilateral ear discharge for two months, mild conductive hearing loss in the right ear (39 dB threshold), and normal hearing in the left ear (24 dB threshold) with slight reductions at frequencies ≤1000 Hz and ≥4000 Hz. CT imaging revealed mucosal thickening in the Prussak space and bilateral mastoid air cells with sclerotic edges, with no cholesteatoma detected. After type II endoscopic tympanoplasty, the patient showed significant improvement, with the cessation of ear discharge and no major complications. Implications: This case highlights the importance of early diagnosis and timely intervention in managing CSOM, demonstrating that type II endoscopic tympanoplasty is an effective, minimally invasive surgical option to repair tympanic membrane perforations and prevent further complications, such as more severe hearing loss. Novelty and Contribution: This case report provides a new contribution to the management of safe type CSOM, emphasizing the success of type II endoscopic tympanoplasty as a less invasive surgical alternative to traditional methods, especially for patients with mild conductive hearing loss and recurrent ear infections.